Faktor yang Mempengaruhi Alih Fungsi Lahan Daerah Resapan Air Kecamatan Cimenyan sebagai Bagian dari Kawasan Bandung Utara (KBU) - Bagas Wijayakusuma; Hani Burhanudin (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract. Water catchment areas are important areas to control to maintain the balance of the hydrological cycle and prevent natural disasters. Many water catchment areas (DRA) have changed their function into built-up land which has resulted in a reduction in the area of the water catchment area itself as is the case in Cimenyan District which is a water catchment area. North Bandung (KBU). The North Bandung area (KBU) itself should act as a counterweight to the special environment in the Greater Bandung area. Looking at the problems related to the conversion of water catchment areas in the North Bandung area (KBU), the authors argue that "Factors influencing the transfer The function of the Cimenyan District Water Catchment Area as Part of the North Bandung Area (KBU)” needs to be done.The purpose of the research was to find out the area of the water catchment area and how much land has been converted to other uses and how to solve this problem because if the area and identify what factors make water catchment land in Cimenyan sub-district change its function from its designation. The method used is the mixed method using methods including literature studies, scientific journal interviews, observation, and also documentation which will later be analyzed using spatial methods and multiple linear regression analysis.From the research that has been done, the authors conclude that there has been a change in land use in the Cimenyan District water catchment area of 31.9 Ha which has changed its designation to built-up land. The change in the function of the water catchment area in Cimenyan District is also caused by 4 influencing factors, namely economic growth, population growth, population migration, and facilities and infrastructure. Abstrak. . Kawasan Resapan Air merupakan kawasan penting untuk dikendalikan untuk menjaga keseimbangan siklus hidrologi dan pencegahan bencana alam.Banyak Daerah Resapan Air (DRA) yang mengalami alih fungsi menjadi lahan terbangun yang mengakibatkan berkurangnya luas pada kawasan resapan air itu sendiri seperti halnya pada Kecamatan Cimenyan yang merupakan Kawasan Bandung Utara (KBU).Seharusnya Kawasan Bandung Utara (KBU) ini sendiri bersifat sebagai penyeimbang lingkungan khusus nya pada daerah Bandung Raya.Melihat permasalahan terkait alih fungsi lahan resapan air di Kawasan Bandung Utara ( KBU ) maka penulis berpendapat bahwa “ Faktor yang mempengaruhi Alih Fungsi Lahan Daerah Resapan Air Kecamatan Cimenyan Sebagai Bagian Dari Kawasan Bandung Utara (KBU)” perlu dilakukan. Tujuan penelitian yang diambil yaitu ingin mengetahui luasan kawasan resapan air dan berapa banyak lahan yang dialih fungsikan ke peruntukan lain dan bagaimana upaya untuk menyelesaikan permasalahan tersebut karena jika Kawasan dan mengidentifikasikan faktor apa saja yang membuat lahan resapan air di kecamatan cimenyan beralih fungsi dari peruntukan nya . Metode yang dipakai adalah mix method dengan menggunakan metode antara lain studi literatur, jurnal ilmiah wawancara, observasi, dan juga dokumentasi yang nanti nya akan dianalisis menggunakan metode spasial dan analisis regresi liner berganda .Dari penelitian yang telah di lakukan,penulis menyimpulkan adanya alih fungsi lahan pada kawasan resapan air Kecamatan Cimenyan sebesar 31.9 Ha yang berubah peruntukan menjadi lahan terbangun. adanya alih fungsi lahan Kawasan Resapan Air di Kecamatan Cimenyan ini juga disebabkan oleh 4 faktor yang mempengaruhi, yaitu pertumbuhan ekonomi pertumbuhan penduduk, migrasi penduduk dan sarana dan prasarana